Enhanced Hydrothermal Stability of γ-Al2O3 Catalyst Supports with Alkyl Phosphonate Coatings - Van Cleve, Tim; Underhill, Devon; Veiga Rodrigues, Mariana [UNESP]; Sievers, Carsten [UNESP]; Medlin, J. Will (American Chemical Society (ACS), 2018)
In this study, monolayers formed from organophosphonic acids were employed to stabilize porous γ-Al2O3, both as a single component and as a support for Pt nanoparticle catalysts, during exposure to hydrothermal conditions. To provide a baseline, structural changes of uncoated γ-Al2O3 catalysts under model aqueous phase reforming conditions (liquid water at 200 °C and autogenic pressure) were examined over the course of 20 h. These changes were characterized by X-ray diffraction, NMR spectroscopy, N2 physisorption, and IR spectroscopy. It was demonstrated that γ-alumina was rapidly converted into a hydrated boehmite (AlOOH) phase with significantly decreased surface area. Deposition of alkyl phosphonate groups on γ-alumina drastically inhibited the formation of boehmite, thereby maintaining its high specific surface area over 20 h of treatment. 27Al MAS NMR spectra demonstrated that hydrothermal stability increased with alkyl tail length despite lower P coverages. Although the inhibition of boehmite formation by the phosphonic acids was attributed primarily to the formation of Al2O3-POx bonds, it was found that use of longer-chain octadecylphosphonic acids led to the most pronounced effect. Phosphonate coatings on Pt/γ-Al2O3 improved stability without adversely affecting the rate of a model reaction, catalytic hydrogenation of 1-hexene.